Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti dengan Metode Problem Based Learning pada Materi Perempuan dan Laki-Laki Diciptakan Sebagai Citra Allah Fase C Kelas V SD Negeri 5 Batas Nangka - Bernadeta Tesa (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve the learning outcomes of Catholic Religious Education and Character Education subjects through the Problem Based Learning (PBL) method for fifth-grade students at SDN 5 Batas Nangka during the 2024/2025 academic year. This research is a Classroom Action Research (CAR) conducted in two cycles, with one meeting in each cycle. Each cycle consists of several stages: planning, action implementation, observation, and reflection. The first and second cycles cover the topics of